2006
DOI: 10.1134/s0006297906070157
|View full text |Cite
|
Sign up to set email alerts
|

Nickase and a protein encoded by an open reading frame downstream from the nickase BspD6I gene form a restriction endonuclease complex

Abstract: We are the first to have isolated a protein (186 amino acid residues) encoded by the open reading frame adjacent to the end of the BspD6I nickase (N.BspD6I) gene. Cleavage of both DNA strands near the sequence recognized by nickase (5 -GAGTC/5 -GACTC) occurs when this protein is added to the reaction mixture containing N.BspD6I. The protein encoded by the open reading frame and the nickase are suggested to be subunits of heterodimeric restriction endonuclease R.BspD6I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…At the time of its detection by us in 2006, endonu clease BspD6I was a unique heterodimeric restriction endonuclease, one subunit of which outside the complex with the other exhibits specific nicking activity [9]. The peculiar properties of restriction endonuclease BspD6I (table) made it possible to classify it as a new type of het erodimeric restriction endonuclease not previously described in the literature.…”
Section: Nicking Endonucleases -Subunits Of Heterodimeric Restrictionmentioning
confidence: 92%
See 1 more Smart Citation
“…At the time of its detection by us in 2006, endonu clease BspD6I was a unique heterodimeric restriction endonuclease, one subunit of which outside the complex with the other exhibits specific nicking activity [9]. The peculiar properties of restriction endonuclease BspD6I (table) made it possible to classify it as a new type of het erodimeric restriction endonuclease not previously described in the literature.…”
Section: Nicking Endonucleases -Subunits Of Heterodimeric Restrictionmentioning
confidence: 92%
“…We have shown for the first time that nicking endonu cleases are a subunit of heterodimeric restriction endonu cleases [9]. Before starting description of these data, we shall briefly consider general characteristics of type II restriction endonucleases.…”
mentioning
confidence: 99%
“…The protein encoded by the open reading frame (ORF) adjacent to the bspD6I gene was found to be the small subunit (ss) of R.BspD6I [13]. It was also shown that ss.BspD6I apart from Nt.BspD6I cannot bind DNA and does not display any nuclease activity.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, double-stranded DNA-specific nicking endonucleases are usually monomeric, with the exception of several structure-specific nicking endonucleases , Komori, et al, 2002. For example, the following linear double-stranded DNA-specific nicking endonucleases are all monomeric proteins (Table 1): N-type nicking endonucleases (e.g, N. BspQI), sequence-specific nicking endonucleases naturally or artificially created by mutating restriction enzymes to lose their dimerization ability (Higgins, et al, 2001, Roberts, et al, 2003, Xu, et al, 2001, Yunusova, et al, 2006, Zheleznaya, et al, 2009); V-type nicking endonucleases (e.g., E. coli Vsr), a short patch MMR nicking endonuclease ; Type I DNA topoisomerases (e.g., E. coli Topo I), an enzyme with a supercoil-relaxing activity (Kirkegaard, et al, 1978); retrotransposon-targeting endonucleases (e.g., L1 endonuclease), a site-specific nicking endonuclease that directs the invasion of the retrotransposon (Feng, et al, 1996, Feng, et al, 1998, Maita, et al, 2007, Weichenrieder, et al, 2004; bovine DNase I, a non-specific nicking endonuclease that functions in the host defense (Suck, et al, 1988); E. coli MutH (Ban, et al, 1998), the MMR nicking endonuclease; bacterial UvrC (Nazimiec, et al, 2001), a nucleotide excision repair nicking endonuclease; bacterial endonuclease V (Dalhus, et al, 2009), a deaminated DNAspecific nicking endonuclease; and bacterial and eukaryotic AP endonucleases (Hosfield, et al, 1999, Mol, et al, 2000, an abasic site-specific nicking endonuclease. Known DNA repair systems other than MMR all adopt a monomeric nicking endonuclease to introduce the entry point for the excision reaction.…”
Section: Bacterial Mutl Is a Homodimeric Nicking Endonucleasementioning
confidence: 99%
“…Therefore, the dimerization ability of the MutL Cterminal domain might be related to the strand-discrimination mechanism of bacterial MMR. (Higgins, et al, 2001, Roberts, et al, 2003, Xu, et al, 2001, Yunusova, et al, 2006 2009) V-type nicking endonucleases (e.g., E. coli Vsr) DNA repair 4 and other Methylated DNA Monomer (Kirkegaard, et al, 1978) Retrotransposontargeting endonucleases 1 (e.g., L1 endonuclease)…”
Section: Bacterial Mutl Is a Homodimeric Nicking Endonucleasementioning
confidence: 99%